ANALISIS TINDAK TUTUR TIDAK LANGSUNG DALAM FILM BLACK PANTHER : WAKANDA FOREVER - Kurniawan, Amandito Resti; Sumardiono, Sumardiono (English Education Department Slamet Riyadi University Surakarta, 2024)
This research was conducted to analyze and find out the speech act that occured in Black Panther : Wakanda Forever’s movie. In this research, the objectives of the research are as follows (1) To analyze the types of indirect speech act uttered by characters in Black Panther : Wakanda Forever Movie. (2) To analyze the illocutionary act of indirect speech act from each utterance that implied in Black Panther : Wakanda Forever Movie. The researcher conducted this research in the library of Slamet Riyadi University. The method that used in this research was qualitative descriptive and data in this research were collected through documentation and observation. The researcher watched the ‘Black Panther : Wakanda Forever’ movie several times, read the transcript of the ‘Black Panther : Wakanda Forever’ movie, and then marked the dialogue and identified the the types of indirect speech act and the illocutionary act of indirect speech act from each utterance that implied in Black Panther : Wakanda Forever Movie. The findings of the research shows that in ‘Black Panther : Wakanda Forever’ movie, there are 74 utterances of indirect speech act. These 74 utterances are divided into two types which is declarative and interogative sentence. There are 52 declarative sentence that were found which consisted with 22 sentence of commanding act, 11 refusing act, 16 suggesting act, and 3 inviting act. As for the interogative sentence, there were 22 sentence consisted of 13 commanding act, 2 refusing act, 4 suggesting act, and 3 refusing act. The researcher analyzed that there were three types of indirect speech act found in ‘Black Panther : Wakanda Forever’ movie which is declarative, interogative, and imperative. Declarative sentence were dominant with 52 sentence gathered from the movie, as for the illucotionary act commanding act were dominant with 35 sentence gathered from the movie. Keywords : Indirect speech act, Illocutionary Acts, Qualitative Research